2005
DOI: 10.1590/s1415-43662005000400022
|View full text |Cite
|
Sign up to set email alerts
|

Otimização do processo de secagem osmótica na obten ção de produtos secos da manga Tommy Atkins

Abstract: Frutas tropicais como a manga (Mangifera indica L.) uma das mais populares do mundo, embora muito apreciadas, são altamente perecíveis e requer técnicas especiais para sua conservação e comercialização, razão por que se objetivou otimizar seu processo de secagem osmótica e estudar o efeito da temperatura, concentração de sacarose e tempo de imersão, em relação à perda de água e ganho de sólidos. A influência de cada variável e sua interação sobre as respostas, foram avaliada através da análise de variância (te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…Osmotic dehydration of mango showed that the temperature and osmotic solution concentration were the dominant process variables that affected the loss of water in mangos (Almeida et al 2005). Osmotic dehydration with glucose solution reduced the effective diffusivity in mango drying by 67%.…”
Section: Malay Applementioning
confidence: 99%
“…Osmotic dehydration of mango showed that the temperature and osmotic solution concentration were the dominant process variables that affected the loss of water in mangos (Almeida et al 2005). Osmotic dehydration with glucose solution reduced the effective diffusivity in mango drying by 67%.…”
Section: Malay Applementioning
confidence: 99%
“…Figure 1 (A) shows that the significant effects for WL, at 5% of significance level, were temperature and concentration of dehydration solution: both effects have a strong influence on water loss, because they are positive and proximal. [9] [14], studying osmotic dehydration of tomatoes and mangoes (of the variety Tommy), respectively, also found out that the process temperature and the concentration of the dehydrating solution were among the significant and positive factors in water loss. However, [15] treated pineapples with osmotic solutions in various concentrations and obtained a constant reduction of the water content, regardless of the osmotic treatment used.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the optimization of the dehydration process is best attained through the variable GS/WL. According to [9], the optimization is reached in the region where you have the highest WL and lowest GS, so that the ratio GS/WL is minimal.…”
Section: Mathematical-statistical Treatment Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Os cálculos de perda de água, ganho de sólidos e relação ganho de sólidos-perda de água, no processo de desidratação osmótica, foram obtidos por meio das equações indicadas por Almeida et al (2005).…”
Section: Methodsunclassified